Design and performance evaluation of Core Flow Monitoring Mechanisms for PFBR. (August 2016) - Sabih, Muhammad; Sureshkumar, S.; Patri, Sudheer; Shivakumar, N.S.; Ravichandran, N.; Thakur, C.L.; Paunikar, Vishal D.; Vijayashree, R.; Sureshkumar, V.A.; Meikandamurthy, C.; Noushad, I.B.; Padmakumar, G.; et al.
Highlights: A scheme for measuring the flow exiting the core subassemblies is proposed. The requisite features of the carrier mechanism are highlighted. Out-of-pile tests carried out to qualify the system are presented. Tests confirm that the system meets the required performance characteristics. Abstract: In this paper, the scheme adopted for off-line monitoring of fuel/blanket sub-assemblies, by measuring the coolant flow rate at sub-assembly exit, in a typical sodium cooled fast breeder reactor is presented. In Prototype Fast Breeder Reactor (PFBR), the temperature of sodium exiting from all the fuel sub-assemblies is monitored by core temperature monitoring system for detecting any flow blockage during reactor operation. However, such online monitoring of blanket sub-assembly outlet temperature was not envisaged. Instead, offline monitoring is proposed, which involves measuring the flow rate of sodium exiting from blanket sub-assemblies during re-fuelling of reactor. A flow measuring system is proposed for measuring sodium flow from blanket sub-assemblies. In addition, the sodium flow from Fuel and storage sub-assemblies is also measured during commissioning stage in order to identify any blockage in the hydraulic paths of respective sub-assemblies. The flow measuring system employs Core Flow Monitoring Mechanism (CFMM) equipped with Eddy Current Flow Sensor (ECFS) for sodium flow measurement. The system needs two CFMMs, one for fuel sub-assemblies and another for blanket and storage sub-assemblies. The necessary experimental studies were carried out for generating data needed for sodium flow estimation and to resolve uncertainties in the design of CFMM. Experimental studies include hydraulic studies and sodium calibration of ECFS. Subsequently, integrated assembly testing of CFMM was carried out to demonstrate the safe operation of the mechanisms before clearing for erection on pile. After successful completion of all the tests, both the CFMM were erected on pile. This paper discusses the detailed design features of CFMM and the developmental activities carried out to qualify the mechanism for reactor use.